XBP1 variant 1 promotes mitosis of cancer cells involving upregulation of the polyglutamylase TTLL6. Issue 15 (25th March 2022) - Zhong, Yongwang; Yan, Wenjing; Ruan, Jingjing; Fang, Mike; Yu, Changjun; Du, Shaojun; Rai, Ganesha; Tao, Dingyin; Henderson, Mark J; Fang, Shengyun
Abstract: XBP1 variant 1 (Xv1) is the most abundant XBP1 variant and is highly enriched across cancer types but nearly none in normal tissues. Its expression is associated with poor patients' survival and is specifically required for survival of malignant cells, but the underlying mechanism is not known. Here we report that Xv1 upregulates the polyglutamylase tubulin tyrosine ligase-like 6 (TTLL6) and promotes mitosis of cancer cells. Like the canonical XBP1, Xv1 mRNA undergoes unconventional splicing by IRE1α under endoplasmic reticulum stress, but it is also constitutively spliced by IRE1β. The spliced Xv1 mRNA encodes the active form of Xv1 protein (Xv1s). RNA sequencing in HeLa cells revealed that Xv1s overexpression regulates expression of genes that are not involved in the canonical unfolded protein response, including TTLL6 as a highly upregulated gene. Gel shift assay and chromatin immunoprecipitation revealed that Xv1s bind to the TTLL6 promoter region. Knockdown of TTLL6 caused death of cancer cells but not benign and normal cells, similar to the effects of knocking down Xv1. Moreover, overexpression of TTLL6 partially rescued BT474 cells from apoptosis induced by either TTLL6 or Xv1 knockdown, supporting TTLL6 as an essential downstream effector of Xv1 in regulating cancer cell survival. TTLL6 is localized in the mitotic spindle of cancer cells. Xv1 or TTLL6 knockdown resulted in decreased spindle polyglutamylation and interpolar spindle, as well as congression failure, mitotic arrest and cell death. These findings suggest that Xv1 is essential for cancer cell mitosis, which is mediated, at least in part, by increasing TTLL6 expression.